Generalized Anxiety Disorder as Accentuated in Ann Beattie’s Shifting - Saputro, Dimas Eko; Rosyadi, Machfianita Mirza Ayu; Oktafiani, Adelia Putri; Pujimahanani, Cahyaningsih; Pasopati, Rommel Utungga (Universitas Pendidikan Indonesia, 2024)
Generalized anxiety disorder is an anxiety disorder commonly experienced in excessive worry by some people with trauma. In the short story entitled Shifting written by Ann Beattie, Natalie is worried about her marriage because Natalie thinks that Larry's mother will not approve of their marriage, this is because Natalie is rarely accompanying Larry. Then, how are generalized anxiety disorders accentuated in Ann Beattie’s Shifting? In analysis, the main character in this story is over-worrying that makes herself being different in the view of the others. The language that she knows has been over consumed that she has been swallowed by the language itself. In conclusion, the short story indicates how any disorder may come from any small worry. If the worrying is not finished, it could be piled up and be shaped into further anxiety that disturbs life of being individuals and parts of societies.